Social Movements as Parsimonious Explanations for Implicit and Explicit Attitude Change. (February 2023) - Sawyer, Jeremy E.; Gampa, Anup
Recently, interest in aggregate and population-level implicit and explicit attitudes has opened inquiry into how attitudes relate to sociopolitical phenomenon. This creates an opportunity to examine social movements as dynamic forces with the potential to generate widespread, lasting attitude change. Although collective action remains underexplored as a means of reducing bias, we advance historical and theoretical justifications for doing so. We review recent studies of aggregate attitudes through the lens of social movement theory, proposing movements as a parsimonious explanation for observed patterns. We outline a model for conceptualizing causal pathways between social movements and implicit and explicit attitudes among participants, supporters, bystanders, and opponents. We identify six categories of mechanisms through which movements may transform attitudes: changing society; media representations; intergroup contact and affiliation; empathy, perspective-taking, and reduced intergroup anxiety; social recategorization; and social identification and self-efficacy processes. Generative questions, testable hypotheses, and promising methods for future work are discussed.